2000
DOI: 10.1054/bjoc.2000.1249
|View full text |Cite
|
Sign up to set email alerts
|

The rate of the founder Jewish mutations in BRCA1 and BRCA2 in prostate cancer patients in Israel

Abstract: Inherited predisposition occurs in 5–10% of all prostate cancer (CaP) patients, but the genes involved in conferring genetic susceptibility remain largely unknown. Several lines of evidence indicate that germline mutations in BRCA1 and BRCA2 might be associated with an increased risk for CaP. Three mutations in these two genes (185delAG and 5382InsC ( BRCA1 ) and 6174delT ( BRCA2 ) occur in about 2.5% of the general Ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Of note, had we excluded patients with personal or familial history of BC from the patient cohort as well as from the control group analysed, the lack of association between these mutations and CRC would be even more striking. Taken together with the recent publications showing these specific mutations do not increase the risk for prostate cancer in this ethnic group (Lehrer et al, 1998;Hubert et al, 1999;Vazina et al, 2000), we can conclude that the predominant Ashkenazi Jewish BRCA1 and BRCA2 mutations do not contribute to the pathogenesis of CRC. Thus, it seems that the two major indications for performing BRCA1/2 genetic testing in men are the personal risk for developing BC (Struewing et al, 1999) and the risk of transmitting the mutated alleles to their daughters.…”
Section: Discussionsupporting
confidence: 78%
“…Of note, had we excluded patients with personal or familial history of BC from the patient cohort as well as from the control group analysed, the lack of association between these mutations and CRC would be even more striking. Taken together with the recent publications showing these specific mutations do not increase the risk for prostate cancer in this ethnic group (Lehrer et al, 1998;Hubert et al, 1999;Vazina et al, 2000), we can conclude that the predominant Ashkenazi Jewish BRCA1 and BRCA2 mutations do not contribute to the pathogenesis of CRC. Thus, it seems that the two major indications for performing BRCA1/2 genetic testing in men are the personal risk for developing BC (Struewing et al, 1999) and the risk of transmitting the mutated alleles to their daughters.…”
Section: Discussionsupporting
confidence: 78%
“…It demonstrated that BRCA2 mutation carriers have a relative risk (RR) of PRCA of 4.65 rising to 7.33 below the age of 65 years and BRCA1 mutation carriers have an RR of PRCA of 1.82 under the age of 65 years (BCLC, 1999; Thompson et al, 2002). Similar data have been recorded in the AJ population (Struewing et al, 1997;Warner et al, 1999;Giusti et al, 2003), although smaller clinical studies have generally not demonstrated an increased frequency of founder BRCA1/2 mutations among Jewish men with PRCA (Lehrer et al, 1998;Hubert et al, 1999;Nastiuk et al, 1999;Vazina et al, 2000). In the current data set, six men were identified from a previous study conducted at The Institute of Cancer Research, as described in the Materials and Methods section.…”
Section: Discussionmentioning
confidence: 71%
“…It has been estimated that ,2% of this population carries at least one of these mutations. [77][78][79][80] Even in this population, the results of these epidemiological studies have been contradictory, but many of them were underpowered, due to small sample size or lack of covariate information. 22,[81][82][83][84][85][86] Another BRCA2 founder mutation that has been extensively studied is the Icelandic BRCA2 999del5 mutation.…”
Section: Discussionmentioning
confidence: 96%